Comparison of the effectiveness of two styles of case-based learning implemented in lectures for developing nursing students’ critical thinking ability: A randomized controlled trial - Hong, Shaohua; Yu, Ping (International journal of nursing studies, 2017)
To explore and compare the effectiveness of two styles of case-based learning methods, unfolding nursing case and usual nursing case, implemented in lectures for developing nursing students’ critical thinking ability. 122 undergraduate nursing students in four classes were taught the subject of medical nursing for one year. Two classes were randomly assigned as the experimental group and the other two the control group. The experimental group received the lectures presenting unfolding nursing cases and the control group was taught the usual cases. Nineteen case-based lectures were provided in 8 months in two semesters to each group. The two groups started with a similar level of critical thinking ability as tested by the instrument of Critical Thinking Disposition Inventory—Chinese version (CTDI-CV). After receiving 19 case-based learning lectures for 8 months, both groups of students significantly improved their critical thinking ability. The improvement in the experimental group was significantly higher than that in the control group (with the average total score of 303.77±15.24 vs. 288.34±13.94, p<0.05). The experimental group also had significantly better improvement in six out of seven dimensions whereas the control group showed improvement in only three out of seven dimensions of CTDI-CV. The study suggests the feasibility of implementing case-based learning in lectures. Unfolding nursing cases appear to be significantly more effective than the usual nursing cases in developing undergraduate nursing students’ critical thinking ability in the subject of medical nursing. Further research can implement the unfolding nursing cases in other nursing subjects.